The Hermit in German Literature From Lessing to Eichendorff - John Fitzell, Henry (UNC Studies in the Germanic Languages and Literatures, 1961)
In this thorough study of the figure of the hermit in the works of German writers Fitzell analyzes characters in works by Lessing, Goethe, Klinger, Hoffmann, Wieland, Eichendorff and others. The author argues that the figure of the hermit characterizes the quality of inwardness and withdrawal from society characteristic of German literature, and shows how this quality was represented in the age of Goethe.